2012
DOI: 10.1016/j.gie.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Sex and racial disparities in duodenal biopsy to evaluate for celiac disease

Abstract: Background Celiac disease (CD) is common but under-diagnosed in the United States. Serological screening studies indicate that, although CD occurs at the same frequency in both genders, women are diagnosed more frequently than men (2:1). CD is less frequently diagnosed among black patients, though the seroprevalence in this group is not known. Objective to measure the rates of duodenal biopsy during esophagogastroeduodenoscopy (EGD) for symptoms consistent with CD. Design Retrospective cohort study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 32 publications
4
41
1
Order By: Relevance
“…But these data show that it is possible for CD patients to undergo multiple encounters with healthcare providers, including gastroenterologists, and undergo invasive testing including endoscopy and biopsy, while still eluding a CD diagnosis. Our observations are not unexpected because previous studies of large national databases have shown that patients undergoing EGD with symptoms compatible with CD often do not undergo duodenal biopsy, 8 and that the majority of patients who have a duodenal biopsy do not have the recommended number of specimens submitted. 9 Most of these patients with missed/incident CD had a clinical indication for dyspepsia or esophageal reflux during their prior EGD.…”
Section: Discussionsupporting
confidence: 59%
“…But these data show that it is possible for CD patients to undergo multiple encounters with healthcare providers, including gastroenterologists, and undergo invasive testing including endoscopy and biopsy, while still eluding a CD diagnosis. Our observations are not unexpected because previous studies of large national databases have shown that patients undergoing EGD with symptoms compatible with CD often do not undergo duodenal biopsy, 8 and that the majority of patients who have a duodenal biopsy do not have the recommended number of specimens submitted. 9 Most of these patients with missed/incident CD had a clinical indication for dyspepsia or esophageal reflux during their prior EGD.…”
Section: Discussionsupporting
confidence: 59%
“…In view of these facts, diagnosis of or confusion with IBS at best partially explains the longer diagnostic delay in women. Diagnostic awareness of CeD in physicians performing upper gastrointestinal endoscopy does not seem to be lower for women, since duodenal biopsies were significantly less often obtained in men then in women [22]. One might thus speculate, that the discrepancy according to gender is related to the initiation of a proper evaluation and diagnostic testing in response to reported symptoms rather than specific testing for CeD once a medical evaluation has been initiated.…”
Section: Discussionmentioning
confidence: 98%
“…Some patients have undergone EGD in the 5 years preceding their diagnosis without having duodenal biopsies [23]. Hence, the number of patients who undergo biopsies is still insufficient, leading to missed cases and a delay in the diagnosis [24]. The current study used parallel biopsy, serology, and prospective collection of potential risk factors in a cross-sectional sample of patients presenting for EGD to determine 1) the reliability of standard clinical judgement, 2) endoscopic findings, and 3) serologic testing to diagnose celiac disease (confirmed by positive histological evidence).…”
mentioning
confidence: 99%